2011
DOI: 10.1097/aln.0b013e318216ea0c
|View full text |Cite
|
Sign up to set email alerts
|

The Quaternary Lidocaine Derivative, QX-314, Exerts Biphasic Effects on Transient Receptor Potential Vanilloid Subtype 1 Channels In Vitro 

Abstract: Background: Transient receptor potential vanilloid subfamily member 1 (TRPV1) channels are important integrators of noxious stimuli with pronounced expression in nociceptive neurons. The experimental local anesthetic, QX-314, a quaternary (i.e., permanently charged) lidocaine derivative, recently has been shown to interact with and permeate these channels to produce nociceptive and sensory blockade in animals in vivo. However, little is known about the specific interactions between QX-314 and TRPV1 channels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…These findings are in good agreement with an earlier observation that capsaicin-evoked TRPV1 inward currents can be inhibited by extracellular lidocaine in mammalian human embryonic kidney 293t cells, although with significantly lower potency (Leffler et al, 2008). Furthermore, we have recently shown that the extracellular administration of the quaternary lidocaine derivative, QX-314, inhibits TRPV1-mediated currents in X. laevis oocytes (Rivera-Acevedo et al, 2011). Taken together, these results suggest that it is a general trait of titratable LAs to inhibit TRPV1-mediated inward currents.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings are in good agreement with an earlier observation that capsaicin-evoked TRPV1 inward currents can be inhibited by extracellular lidocaine in mammalian human embryonic kidney 293t cells, although with significantly lower potency (Leffler et al, 2008). Furthermore, we have recently shown that the extracellular administration of the quaternary lidocaine derivative, QX-314, inhibits TRPV1-mediated currents in X. laevis oocytes (Rivera-Acevedo et al, 2011). Taken together, these results suggest that it is a general trait of titratable LAs to inhibit TRPV1-mediated inward currents.…”
Section: Discussionsupporting
confidence: 80%
“…We previously showed that the quaternary lidocaine derivative, QX-314, inhibits capsaicin-activated TRPV1 channels (Rivera-Acevedo et al, 2011). Benzocaine, on the other hand, which features a lipophilic aromatic moiety that is shared with both lidocaine and QX-314 but lacks a nitrogen that can be charged under physiological conditions, did not inhibit TRPV1 currents (see above).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that TRPV1 channels, expressed in Xenopus leavis oocytes, are reversibly inhibited by the quaternary ammonium compound QX-314 with micromolar affinity. 16 In contrast, our follow-up study demonstrated that the amplitudes (from 100 nA to 15 μA), which we assumed to roughly correlate with channel expression levels. In single drug application experiments, 1 or 10 μM QX-314 were co-applied with an approximate EC 50 concentration of capsaicin (15 μM) to oocytes expressing varying levels of TRPV1 channels.…”
mentioning
confidence: 45%
“…One obvious candidate is the pore domain, with its selectivity filter being the final integrator of the diverse stimuli acting on the ion channel, ultimately biasing the open-closed equilibrium. To this end, we and others have demonstrated extracellular TRPV1 inhibition by charged or chargeable ammonium compounds, 16,17 and we have recently shown that these compounds likely target the channel pore.…”
Section: Introductionmentioning
confidence: 99%